An Artist’s Sketchbook: the former altarpiece of Goa Cathedral (India) attributed to the painter Garcia Fernandes – iconographic and stylistic inf luences and underdrawing study - Antunes, Vanessa (2022)
Goa Cathedral former altarpiece, attributed to Garcia Fernandes and made around 1538, is one of the oldest western pictorial works in India. It is a work of great importance in the establishment of the conquest of Goa by the Portuguese but also for understanding the inf luence of Portuguese painting overseas. Goa Cathedral former altarpiece is revealed as a crucial study source of Garcia Fernandes' creative process. There is evidence in the vigorous underdrawing of these paintings, of the existence of different types of drawing, as well as abandoned iconographic themes, or formal alterations of compositions. The iconographic and stylistic study evidences north and south-European inf luences in the choice and representation of the themes around the Martírio de Santa Catarina. In the present study, this work is compared in the making of the underdrawing with other works attributed to Garcia Fernandes.